Gambaran Data Demografi Pemberian Asi Pada Wanita Pekerja Swasta Di Desa Jetis, Wilayah Kerja Puskesmas Baki 1 Kabupaten Sukoharjo - Permatasari, Putri, Sulastri, S.Kp., M.Kes, Wachidah Yuniartika, S.Kep., Ns (2015)
Breast milk is the best natural nutrition for babies. Breast milk contains energy and nutrients needed during the first six months of a baby 's life . Breastfeeding is very important because it can be beneficial for the baby and mother. The success of exclusive breastfeeding may be influenced by factors of mothers, babies and families. Maternal characteristics that can affect the success of exclusive breastfeeding in the form of age, the number of hours worked, education level, income and parity. The purpose of this research to describe demographic data of breastfeeding women workers in the private sector Jetis village, Baki 1 health center Sukoharjo. The research method is descriptive analytic. This type of research is quantitative research and using survey approach. The data collection is done with questionaires given to respondents. Whereas the samples taken into account are private worker mothers raising six to eight month old babies. Total sampling is used in this study with the total of 30 respondents. Data analysis technique in this research is table of frequency distribution. The results that the breastfeeding woman private sector workers who have infants aged 6-8 months, exclusive breastfeeding as much as 13,3%. According to demographic data, exclusive breastfeeding by working women at the range age of 20 to 35 year old, had her first child, having Junior and Senior High School as their final education, income more than 1.000.000, and having 8 hour a day jobs. Exclusive breastfeeding of 13,3% given by mothers who often express the milk at home, 6,7% exclusive breastfeeding by mothers with full facilities in the company, and by 10% exclusive breastfeeding by mothers who received support from superiors.